The gasoline price and the commuting behavior: Towards sustainable modes of transport - Ignacio Belloc; José Ignacio Giménez-Nadal; José Alberto Molina (Global Labor Organization (GLO), 2022)
This paper analyzes how gasoline price is related to the time workers in the US spend commuting by private vehicle, public transport, walking, or cycling. Using data from the American Time Use Survey for the years 2003-2019, and collecting data on gasoline price by state and year, we find that higher gasoline prices are related to less commuting by private car, and more commuting by public transport, walking, and cycling, the latter being transportation alternatives that are more eco-friendly. A 1% increase in gas prices is associated with an increase of 0.325%, 0.568% and 0.129% in the commuting time by public and physical modes (walking and cycling), respectively. By contrast, a decrease of 0.638% is found in the proportion of commuting done by private car. Furthermore, the elasticity differs by urban characteristics, showing relatively larger values in urban areas for private and public modes. By analyzing the relationship between commuting time, and gasoline prices in the US, our results may serve to inform future policies aiming to develop a low-carbon transport system, especially in urban areas where workers may be more affected by gasoline prices (and thus taxation).
Keywords: R40; J1; J22; D1; Q4; R4; 330; commuting time; gasoline price; commuting mode; urban areas; American Time Use Survey